2013
DOI: 10.1152/jn.00086.2013
|View full text |Cite
|
Sign up to set email alerts
|

Wrist torque estimation during simultaneous and continuously changing movements: surface vs. untargeted intramuscular EMG

Abstract: Kamavuako EN, Scheme EJ, Englehart KB. Wrist torque estimation during simultaneous and continuously changing movements: surface vs. untargeted intramuscular EMG. J Neurophysiol 109: 2658-2665, 2013. First published March 20, 2013 doi:10.1152/jn.00086.2013In this paper, the predictive capability of surface and untargeted intramuscular electromyography (EMG) was compared with respect to wrist-joint torque to quantify which type of measurement better represents joint torque during multiple degrees-of-freedom (Do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 44 publications
2
39
1
Order By: Relevance
“…The predictive capability of intramuscular EMG with respect to force has also been shown during single (Kamavuako et al, 2012b) and simultaneous (Kamavuako et al, 2012a) DoF. Recently a comparison between surface and intramuscular using simultaneous and continuously changing torque has been reported (Kamavuako et al, 2013b). It was indicated that both methods were able to track the torque profile well, but had some trouble (particularly intramuscular EMG) in estimating the exact amplitude.…”
Section: Introductionmentioning
confidence: 98%
“…The predictive capability of intramuscular EMG with respect to force has also been shown during single (Kamavuako et al, 2012b) and simultaneous (Kamavuako et al, 2012a) DoF. Recently a comparison between surface and intramuscular using simultaneous and continuously changing torque has been reported (Kamavuako et al, 2013b). It was indicated that both methods were able to track the torque profile well, but had some trouble (particularly intramuscular EMG) in estimating the exact amplitude.…”
Section: Introductionmentioning
confidence: 98%
“…Such approaches have included conventional myoelectric control methods [8, 9] and nonlinear regression methods [10]. Notably, intramuscular EMG obtained from Implantable Myoelectric Sensors (IMES ® ) in the forearm were used to simultaneously control prosthetic wrist rotation and a 2-DOF hand [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Most recent studies on intramuscular EMG control have instead focused on the machine-learning algorithms that are also being pursued for surface EMG (Kamavuako et al, 2012, Kamavuako et al, 2013b, Smith and Hargrove, 2013). However, the few studies of parallel dual-site control have been promising.…”
Section: Introductionmentioning
confidence: 99%